APLIKASI MODEL ROLE PLAYING SEBAGAI UPAYA PEMBELAJARAN NILAI DALAM PENDIDIKAN IPS SD/MI - Zuhriyah, Indah Aminatuz (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
Value is a conviction or believes that become the basic for a person or a group of person to choose their action, or appraise something meaningful or something unmeaning for their live.Â  This interpretation means that value is a characteristic attributed to something related to subject (human as the provider of value). Social values in social science education in elementary school (SD/MI) can be applied trough role playing. Role playing is learning processes in which the students do something have done by other people. That other people maybe is a president, ministry, prominent figure of society, law official, teachers, the owner of other professions, officials, or even the ordinary people. The important thing from this learning process is that students try to think, feel the emotion, and act not as their own self but as others. By occupy and inspire the role, students are going to understand why such kind of action should be done, what kind of value underlying that consideration, and how the object people face that kind of situation. Keyword: value education, role playing, social science.